Poutine Dynamics - Fabien-Ouellet, Nicolas (Cuizine, 2016)
Taking everyone by surprise, poutine—an unpretentious Quebecois dish originally made of fries, cheese curds and brown gravy—found its way onto the Canadian State Dinner menu organized by the White House in March 2016. Drawing on my personal relationship with poutine, this paper intends to expose how poutine has managed to enact a form of social mobility. The tasting experience of poutine is first deconstructed through its taste ‘on the tongue’ and its taste as a dynamic social process, to investigate poutine’s palatability and mainstream appeal. Through this tasting analysis, poutine emerges as a new(er) and distinct way to consume food that is increasingly adopted and adapted. A working definition of poutine as a new dish classification label in its own right (just like sandwiches, dumplings, soups, flatbreads or sushi) is proposed. The social mobility of other foods (e.g. lobster, kimchi, garlic, and sushi) is further explored, before discussing how poutine is also connected to a stigma, which weakens the agency of the Quebecois. Using the social identity theory, it appears that Quebecois youth are dismissing this ‘poutine stigma’ through a revaluing approach, which resembles a reappropriation of poutine, not necessarily linguistically (as seen with ‘black’, ‘queer’, or ‘geek’), but rather in a culinary fashion. Coupling poutine’s sociohistorical stigma and its growing Canadization (that is, the presentation, not the consumption per say, of poutine as a Canadian dish), two related situations—the ongoing process of poutine culinary appropriation and the threat of Quebecois cultural absorption by Canadians—are exposed.